Shell Games: The Long-Term Performance of Chinese Reverse-Merger Firms - Lee, Charles M. C.; Li, Kevin K.; Zhang, Ran (The Accounting Review, 2015)
ABSTRACT We examine the financial health and performance of reverse mergers (RMs) that became active on U.S. stock markets between 2001 and 2010, particularly those from China (around 85 percent of all foreign RMs). As a group, RMs are early-stage companies that typically trade over the counter. However, Chinese RMs (CRMs) tend to be more mature and less speculative than either their U.S. counterparts or a group of exchange-industry-size-matched firms. As a group, CRMs outperformed their matched peers from inception through the end of 2013, even after including most of the firms accused of accounting fraud. CRMs that receive private investment in public equity (PIPE) financing from sophisticated investors perform particularly well. Overall, despite the negative publicity, we find little evidence that CRMs are inherently toxic investments. Our results shed light on the risk-performance trade-off for CRMs, as well as the delicate balance between credibility and access in well-functioning markets. JEL Classifications: G34; M41; N20